Evaluation of the Use of Different Solvents for Phytochemical Constituents, Antioxidants, and In Vitro Anti-Inflammatory Activities of Severinia buxifolia. (3rd February 2019) - Truong, Dieu-Hien; Nguyen, Dinh Hieu; Ta, Nhat Thuy Anh; Bui, Anh Vo; Do, Tuong Ha; Nguyen, Hoang Chinh
Abstract : Severinia buxifolia (Rutaceae) is a promising source of bioactive compounds since it has been traditionally used for the treatment of various diseases. The present study aimed at evaluating the impact of different solvents on extraction yields, phytochemical constituents and antioxidants, and in vitro anti-inflammatory activities of S. buxifolia . The results showed that the used solvents took an important role in the yield of extraction, the content of chemical components, and the tested biological activities. Methanol was identified as the most effective solvent for the extraction, resulting in the highest extraction yield (33.2%) as well as the highest content of phenolic (13.36 mg GAE/g DW), flavonoid (1.92 mg QE/g DW), alkaloid (1.40 mg AE/g DW), and terpenoids (1.25%, w/w). The extract obtained from methanol exhibited high capacity of antioxidant (IC50 value of 16.99 μ g/mL) and in vitro anti-inflammatory activity (i.e., albumin denaturation: IC50 = 28.86 μ g/mL; antiproteinase activity: IC50 = 414.29 μ g/mL; and membrane stabilization: IC50 = 319 μ g/mL). The antioxidant activity of the S. buxifolia extract was found to be 3-fold higher than ascorbic acid, and the anti-inflammatory activity of S. buxifolia extract was comparable to aspirin. Therefore, methanol is recommended as the optimal solvent to obtain high content of phytochemical constituents as well as high antioxidants and in vitro anti-inflammatory constituents from the branches of S. buxifolia for utilization in pharmacognosy.